Factors Influencing Taxpayer Compliance in Paying Rural and Urban Land and Building Tax (Case Study of Lotta Village, Pineleng District) - SENDIANG, Melvin Keneth Warguna; SONDAKH, Jullie Jeannete; LAMBEY, Robert (Journal of Governance, Taxation and Auditing, 2024)
Tax is defined as a mandatory contribution paid by the people to the state. The contribution in question is a levy imposed by the government by force based on the law in connection with the government's function of serving the public and realizing public welfare. This research analyzes the factors influencing taxpayer compliance in paying Rural and Urban Land and Building Tax. The sampling technique to be used in this study is cluster random sampling. The research location is in Lotta Village, Pineleng District. This study uses quantitative research. Its object is the Rural and urban land and Building Taxpayers registered in Lotta Village, Pineleng District. The analysis method includes validity testing, reliability testing, classical assumptions testing, hypothesis testing, and multiple linear regression analysis using SPSS version 29. Based on the test results, it can be concluded that the Tax Service variable (X1) and Tax Sanctions variable (X3) significantly influence compliance in paying Rural and Urban Land and Building Tax in Lotta Village, Pineleng District. Tax knowledge (X2) negatively influences compliance in paying Rural and Urban Land and Building Tax in Lotta Village, Pineleng District.